Adaptação de modelo e desenvolvimento de ferramenta para avaliar maturidade industrial em empresas de produtos tangíveis - Fernandes, Ederson Carvalhar (2015)
The tangible products manufacturing industries seek to improve their industrial performance, facing the intense competition scenario. However, the industrial performance is related to the maturity level of the company and its continuous improvement potential to result a differential issue. Mature companies achieve their goals consciously and efficiently, while the immature do not reach the expected results. To know what it demands to improve, it is necessary to diagnose the current situation of the company. Among the main models that allow the industrial maturity assessment, the Capability Maturity Model Integration (CMMI) is one of the most popular and efficient for the Information Technology Industry. Because this model was not developed for a tangible products industrial area, the objective of this study is to adapt all the original model terms to this industrial context, in addition, it is aimed a tool for a self evaluation of a manufacturing company. For this, a literature review on the maturity models, many adaptations of terms in different applications and the existing maturity assessment tools are presented. Through this material, a strategy to adapt the CMMI terms is defined. To reduce the number of terms to be adapted, a questionnaire composed by the terms of CMMI model was produced, which was submitted to 14 different professionals and one academic, in order to identify the terms that would require adaptation. Through the identification of the necessary terms to be adapted, several resources were used to guarantee the effectiveness of adaptation strategy, including: mental maps, glossaries and the expert assistance in the field. After this, the process was validated through new interviews and applications of the instrument with the adapted terms. Alongside the adaptation strategy, a web tool was developed, including the terms in Brazilian Portuguese, from the official CMMI translation, adapted to the manufacturing industrial area. Among the results, the work presents the adaptation strategy to CMMI, showing the model structure after the adaptation, and presenting the tool development to industrial maturity assessment in a simple and fast way, which is tested for a Process Engineer and evaluated through a satisfaction questionnaire.